Regulation of VEGFR3 signaling in lymphatic endothelial cells - Kuonqui, Kevin G.; Campbell, Adana-Christine; Pollack, Bracha L.; Shin, Jinyeon; Sarker, Ananta; Brown, Stav; Park, Hyeung Ju; Mehrara, Babak J.; Kataru, Raghu P. (Frontiers in Cell and Developmental Biology, 2025)
The receptor tyrosine kinase vascular endothelial growth factor (VEGF) receptor 3 (VEGFR3) is the principal transmembrane receptor responsible for sensing and coordinating cellular responses to environmental lymphangiogenic stimuli in lymphatic endothelial cells (LECs). VEGFC and D (VEGFC/D) function as the cognate ligands to VEGFR3 by stimulating autophosphorylation of intracellular VEGFR3 tyrosine kinase domains that activate signal cascades involved in lymphatic growth and survival. VEGFR3 primarily promotes downstream signaling through the phosphoinositide 3-kinase (PI3K) and Ras signaling cascades that promote functions including cell proliferation and migration. The importance of VEGFR3 cascades in lymphatic physiology is underscored by identification of dysfunctional VEGFR3 signaling across several lymphatic-related diseases. Recently, our group has shown that intracellular modification of VEGFR3 signaling is a potent means of inducing lymphangiogenesis independent of VEGFC. This is important because long-term treatment with recombinant VEGFC may have deleterious consequences due to off-target effects. A more complete understanding of VEGFR3 signaling pathways may lead to novel drug development strategies. The purpose of this review is to 1) characterize molecular mediators of VEGFC/VEGFR3 downstream signaling activation and their functional roles in LEC physiology and 2) explore molecular regulation of overall VEGFR3 expression and activity within LECs.